PROSPEK PEMBENTUKAN DAERAH ISTIMEWASUMATERA BARAT DALAM KORIDOR NEGARAKESATUAN REPUBLIK INDONESIA - Putra, Ridwan (Kopertis Wilayah X, 2018)
The State recognizes and respects special or special regional government units regulated by law, then indigenous and tribal peoples and their traditional rights as long as they are alive and in accordance with the developments and principles of the Unitary State of the Republic of Indonesia. The legal basis of this special area is regulated in Article 18B of the 1945 Constitution. The problems studied in this paper are: first, what is the rationale for the establishment of special region of West Sumatra. Second, what is the prospect of establishing a special region of West Sumatra based on the Indonesian constitution. In this research, approach method used is normative juridical. Based on the results of the study and discussion it is concluded that: first, the rationale for the establishment of this special region of West Sumatra is Article 18B of the 1945 Constitution which gives an opportunity to regions that have special or special characteristics with the record of such specificity is still cultivated / the culture is still alive today. Second, the prospect of establishing a special region of western Sumatra based on the Indonesian constitution is: Conceptualization Stage, Formulation of basic concepts around West Sumatra's special region, key reasons, desired community form, community management procedures to achieve the ultimate goal (all materials for manuscript academic and Draft Law of the Province of West Sumatera Special Region Legislation Stage (by legislatures and state officials) Drafting of the Special Province Provincial Law of West Sumatra, the elaboration of the law into a series of implementing regulations such as regional regulations (PERDA) up to jutlak / field in the field for implementing up to the nagari regulations Institutional stage, Stage change of institution or SKPD (work unit of local government) up to institutions in Nagari, or establishment of new institutions / work units according to law and regulations, and the last stage of socialization.